“ENHANCING STUDENTS’ COLLABORATIVE SKILLS THROUGH TECHNOLOGY-ASSISTED EXTRACURRICULAR PROGRAMS” - Djabbarova Nargiza Bakitovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the role of technology-assisted extracurricular programs in improving students’ collaborative skills. The study emphasizes how digital platforms, interactive tools, and multimedia resources can facilitate teamwork, communication, and problem-solving among students. Effective pedagogical strategies for integrating technology into extracurricular activities to foster collaboration are also discussed.